STRATEGI DAN PENGUKURAN KINERJA BADAN RUMAH SAKIT UMUM TABANAN DENGAN PENDEKATAN BALANCED SCORECARD - Antari, Ni Wayan Yoshi; Sudana, I Putu (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine how the linkage between strategy and performance measures BRSU Tabanan with balanced scorecard approach . Data collection methods used were questionnaires and documentation . This study concluded that the strategy of improving financial performance can be achieved with good strategy while strategy of improving quality of care has not achieved the desired results because of poor service quality. BRSU Tabanan should maintain and improve employee empowerment and employee satisfaction so that the quality of service to be better .
Keywords: strategy, performance measurement, balanced scorecard